Raising the profile of care home nursing through collaborative working. (May 2021) - Astle, Anita; Heath, Ros; Sanders, Kate; Jack, Kirsten
Abstract: Aim: To explore the innovative educational practices of two care home teams based in the United Kingdom (UK). Both homes aimed to provide education and developmental opportunities so that they could further deliver effective nursing care to residents. Through such practices, the care homes sought to enhance nursing career development and improve workforce retention. Meeting the long-term care needs of older people remains a challenge and the nursing workforce need to be adequately supported to deliver effective care. Employers have an important role in supporting the educational and developmental needs of nursing staff so that they can fulfil their challenging roles. Conclusion: Using several approaches to nursing education and development, the care homes described in this Discussion Paper were able to show positive impact. Considering the care home workforce shortage and employability churn, it is hoped these ideas can offer inspiration to others in the sector.